Interlayer Friction in Graphene/MoS2, Graphene/NbSe2, Tellurene/MoS2 and Tellurene/NbSe2 van der Waals Heterostructures - Wei, Yaru; Ru, Guoliang; Qi, Weihong; Tang, Kewei; Xue, Taowen (Frontiers in Mechanical Engineering, 2022)
Two-dimensional (2D) materials have a wide range of applications in the field of molecular-level solid lubrication due to their ultrahigh mechanical strength and extremely low friction properties at the nanoscale. In this work, we investigated the interlayer friction properties of four different heterostructures, namely, graphene/MoS2, graphene/NbSe2, α-tellurene/MoS2 and α-tellurene/NbSe2, using a molecular dynamics (MD) method. The effects of a series of influencing factors on the interlayer friction were investigated. The results show that for the four heterostructures, the influence laws of layer number, temperature, and normal load on interlayer friction show consistency. The twist angle can effectively regulate the interlayer friction of these 2D materials, but the superlubricity phenomenon cannot occur for α-Te/MoS2 and α-Te/NbSe2 systems. Furthermore, we address the origin of friction in detail, emphasizing the contribution of edge pinning and interface sliding resistance to the frictional force of the heterostructure. The friction decreases with increasing temperature and sliding speed due to the reduction in the interlayer adhesion force. The present findings provide a deep understanding of friction control and contribute much to the design of robust 2D superlubricity systems.